The Influence Of Hotel Interior, Hotel Customer Process, And Hotel Design On Repurchase Intentions Mediated By Customer Satisfaction - Diomi Shinegi; Anton Wachidin Widjaja (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2022)
The development of sharia hotels is considered as a support for tourism that is not only commercially oriented but always upholds the noble values of religion and customs of a nation. This study is a quantitative study that aims to test the influence of independent variables on dependent variables. The sample in this study was carried out by simple random sampling. The research data was obtained by spreading questionnaires to sharia hotel customers. The collected data were analyzed by path analysis assisted by the Smart PLS application. Smart PLS analysis in this study was carried out in 2 stages, namely outer model and inner model analysis. Inner model analysis for 1) testing the validity and reliability of the instrument and 2) conducting an r square test to determine the percentage of influence. The inner model analysis is carried out to test hypotheses. Based on the test results, it is known that all instruments are declared valid and flexible. Hotel Interior, Hotel Customer Process, and Hotel Design affect customer satisfaction by 94.0%, while Hotel Customer Process and Hotel Design affect customer satisfaction and customer satisfaction affects repurchase intention by 96.1%. The results of hypothesis testing show that the Hotel Customer Process, Hotel interior, and hotel design affect the company's satisfaction, and customer satisfaction can partially mediate the relationship between the hotel customer process, hotel interior, and hotel design to repurchase intention. Upcoming research is expected to add other variables because there are still many factors that affect consumer satisfaction and repurchase intentions of Islamic hotel customers. The reach for research on Islamic hotels can expand and expand widely.